2017
DOI: 10.21037/atm.2017.06.61
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic value of admission red blood cell distribution width in acute pancreatitis: a systematic review

Abstract: Current evidence and findings support that high admission RDW can be used as a biomarker to identify the AP patients who are at high risk of mortality. However, due to the weaknesses of available studies, further well-designed studies with large sample size and various outcome endpoints are needed to rigorously evaluate the prognostic value of RDW in AP.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
47
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(50 citation statements)
references
References 41 publications
(53 reference statements)
1
47
0
2
Order By: Relevance
“…The red cell distribution width (RDW) is a quantitative measure of variability in the size of circulating erythrocytes with higher values reflecting greater heterogeneity in cellular sizes. As a part of complete blood cell count, RDW is generally determined among hospitalized patients because of its simplicity and availability [10,11]. RDW is typically used to differentiate the different causes of anemia [12], however, the present studies have observed that RDW could be used as a predictive marker in various diseases, including cardiovascular disease [11,13], malignant tumors [14,15], acute pancreatitis [16].…”
Section: Introductionmentioning
confidence: 71%
“…The red cell distribution width (RDW) is a quantitative measure of variability in the size of circulating erythrocytes with higher values reflecting greater heterogeneity in cellular sizes. As a part of complete blood cell count, RDW is generally determined among hospitalized patients because of its simplicity and availability [10,11]. RDW is typically used to differentiate the different causes of anemia [12], however, the present studies have observed that RDW could be used as a predictive marker in various diseases, including cardiovascular disease [11,13], malignant tumors [14,15], acute pancreatitis [16].…”
Section: Introductionmentioning
confidence: 71%
“…Red blood distribution width (RDW) is a routine parameter of the complete blood count test, which is easily obtained and inexpensive [166,167]. It is commonly performed in the assessment of almost all patients at the time of admission.…”
Section: Red Blood Cell Distribution Widthmentioning
confidence: 99%
“…Red blood cell distribution width (RDW) represents the variability of form and size in red blood cells of a subject and is a hemogram index that is used for the differential diagnosis of anemia [1]. High RDW has been associated with increased mortality in patients with coronary disease [2], cardiac arrest [3], heart failure [4], pancreatitis [5], liver disease [6], sepsis [7,8], or traumatic brain injury [9].…”
Section: Introductionmentioning
confidence: 99%